How have MOOCs been portrayed in the New Zealand public media? - Rowan Y; Hartnett M (Flexible Learning Association of New Zealand (FLANZ))
Reports of Massive Open Online Courses (MOOCs) hit the news media from 2012 with messages of disruption to existing higher education systems. However, several years on their role is still evolving. Given the power of media to influence acceptance of new ideas, this research investigates New Zealand news media representations of MOOCs to the public. A document analysis of twenty seven newspaper articles published in New Zealand mainstream media between January, 2012 and December, 2016 revealed similar results to overseas research, in that MOOCs are predominantly reported as a catalyst for necessary change to higher education, with higher education commonly discussed in commodified terms. Previously published research focuses on the association of MOOCs and elite universities, whereas this research reveals that MOOCs are considered experimental within New Zealand’s higher education system. While New Zealand media present a more balanced perspective than previous research, dominant themes of MOOCs as revolutionising are likely to foster the public’s acceptance of radical changes to existing higher education structures.
Keywords: massive open online courses; media; MOOCs; New Zealand